An Overview Of Fall Risk Factors, Assessment Measures And Interventions In Older Adults - Marcelo de Maio Nascimento (Brazilian Society of Geriatrics and Gerontology, 2024)
The objective of this study was to present the main factors responsible for falls in older adults, measures for assessing risk, and prevention strategies. This is a qualitative study, developed from the international and national gerontology literature. Two models were created, one including the main fall risk factors and another including common assessment and prevention measures. Five types of intervention procedures were identified: educational, physical, cognitive, exergames and exercise programs. It was concluded that early identification of fall risk is important. The most appropriate intervention methodologies for preventing falls in the elderly include periodic dual and multi-task physical training followed by educational measures. In addition, exercise programs and exergames are effective in preventing falls, especially in congregate housing.